Analisis budaya organisasi menggunakan metode organizational culture assessment instrument (ocai) - Arif Rakhman (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
The Analysis of Organization Culture Used Organizational Culture Assessment Instrument (OCAI) Method at Kaltim Post Samarinda. Supervisor by Dr. Tetra Hidayati, M. Si as the first supervisor and Robiyansyah, SE, M. Sc as second supervisor.This research was done to know about organisational culture this time at Kaltim Post Samarinda,  to know organization culture that be wanted in three years later at Kaltim Post Samarinda, to conclude appropriate recommendation to reach organisational culture that be wanted at Kaltim Post Samarinda.The research was done by data collecting method such as questionnaire, observation and literature study. Whereas, the analyze way is OCAI instrument, where the respondents were asked to fill questionnaire about organisational culture at this time and organisational culture in three years later (that be wanted). The respondents in this research were 47 persons, that they are Kaltim Post Samarinda employees. According to the result of this research that there are similarity of perception between leader and employees that the dominant organisational culture of Kaltim Post Samarinda are clan culture around 32,0 % and 29,2 %, whereas according to leader that organisational culture for three years later will increase on clan around 33,3 %, and according to employee around 31,8 %. Besides, according to employee that organisational culture that will come later, also will increase on hierarchy, which organisational culture in this time around 21,7 % become 22,5 %.